Preparation of enantiopure trans-1,2-cyclohexanediol and trans-2-aminocyclohexanol - Chatterjee, A.; Sasikumar, M.; Joshi, Navalkishore N. (Synthetic Communications, 2007)
Trans-1,2-cyclohexanediol and trans-2-aminocycloxexanol are useful chiral auxiliaries. Simple chemical resolution procedures for these molecules are presented.
Keywords: chemical resolution; chiral auxiliaries; epoxide-cleavage

First asymmetric synthesis of the antiepileptic drug lacosamide (Vimpat (R)) based on a hydrolytic kinetic resolution strategy - Muthukrishnan, Murugan; Mujahid, Mohammad; Sasikumar, M.; Mujumdar, P. (Tetrahedron-Asymmetry, 2011)
An efficient asymmetric synthesis of the new antiepileptic drug, Lacosamide is described in high enantiopurity (>98% ee), using Jacobsen's hydrolytic kinetic resolution strategy as a key step. (C) 2011 Elsevier Ltd. All rights reserved.

Alternate synthesis of enantiomerically pure levetiracetam (Keppra (R)) - Mujahid, Mohammad; Mujumdar, P.; Sasikumar, M.; Kunte, S. S.; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2012)
A simple and efficient synthesis of levetiracetam has been achieved with high enantiopurity (>99%) starting from commercially available benzyl glycidyl ether. The method is amenable for industrial scale-up. (C) 2012 Elsevier Ltd. All rights reserved.

Chiral aziridine ring opening: facile synthesis of (R)-modletine and (R)-phenoxybenzamine hydrochloride - Viswanadh, N.; Velayudham, R.; Jambu, S.; Sasikumar, M.; Muthukrishnan, Murugan (Tetrahedron Letters, 2015)
A simple and efficient synthesis of chiral drugs (R)-mexiletine 1, an anti-arrhythmic drug and (R)-phenoxybenzamine hydrochloride 2, an anti-hypertensive drug has been described via controlled reductive ring opening of chiral aziridine as a key step. The target compounds 1 and 2 were obtained in overall yields of 34% and 10.5%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Aziridine; Mexiletine; Phenoxybenzamine

Detailed study on the thermal, photo-physical and electrochemical properties and OFET applications of D-pi-A-pi-D structured unsymmetrical diketopyrrolopyrrole materials - Bharath, D.; Chithiravel, Sundaresan; Sasikumar, M.; Chereddy, Narendra Reddy; Shanigaram, Balaiah; Bhanuprakash, K.; Krishnamoorthy, K.; Rao, V. Jayathirtha (RSC Advances, 2015)
A series of seven unsymmetrical diketopyrrolopyrrole (DPP) derivatives with donor-pi-acceptor-pi-donor (D-pi-A-pi-D) architecture have been designed, synthesized and well characterised. The effect of the electron donating capacity and extent of electronic conjugation of the end-capping units on the thermal, photo-physical and electrochemical properties of the synthesized materials was thoroughly investigated using various experimental techniques and theoretical calculations. Organic field-effect transistors (OFETs) were fabricated using these materials to obtain their hole/electron transporting characteristics. All these materials showed moderate to good hole transporting ability, and the OFET fabricated using the DPP-derivative with benzofuran and pyrene end groups exhibited a hole mobility of 6.7 x 10(-4) cm(2) V-1 s(-1) with VT of similar to 9 V. The observed photo-physical, electrochemical, thermal, and charge carrier properties of the synthesized DPP-derivatives indicated their applicability in various areas like organic photovoltaics, disposable electronics and biomedical devices.

Alternate synthesis of appetite suppressant (R)-2-benzylmorpholine employing Sharpless asymmetric epoxidation strategy - Viswanadh, N.; Mujumdar, P.; Sasikumar, M.; Kunte, S. S.; Muthukrishnan, Murugan (Tetrahedron Letters, 2016)
An alternate synthesis of (R)-2-benzylmorpholine 1, an appetite suppressant agent has been accomplished starting from readily available trans-cinnamyl alcohol employing Sharpless asymmetric epoxidation strategy as a key step, with an overall yield of 24%. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: (R)-2-Benzylmorpholine; Appetite suppressant; Sharpless asymmetric epoxidation

Role of acceptor strength on OFET properties of small molecular organic semiconducting materials with D-A-D architecture - Sasikumar, M.; Bharath, D.; Kumar, G. Siva; Chereddy, Narendra Reddy; Chithiravel, S.; Krishnamoorthy, K.; Shanigaram, Balaiah; Bhanuprakash, K.; Rao, V. Jayathirtha (Synthetic Metals, 2016)
Two organic semiconducting materials 2,5-didodecyl-3,6-bis(4-(11-dodecyl-11H-benzo[a]carbazol-8yl)phenyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione. (BCDPP) and 1,5-didodecyl-3,7-bis(4-(11-dodecyl-11H-benzo[a]carbazol-8-yl)phenyl)dipyrrolo[3,2-b:3',2'-e]pyrazine-2,6(1H,5H)-dione (BCPzDP) with D-A-D architecture have been designed, synthesized and well characterized. Both the materials have benzocarbazole donor end-capping units. While BCDPP contains well explored diketopyrrolopyrrole (DPP), BCPzDP possesses electron deficient dipyrrolopyrazinedione (PzDP) as acceptor moiety. The importance of the nature of acceptor moiety in tuning the charge transport properties of the synthesized materials is explored. Thermal, photo-physical and electrochemical properties of these materials are measured and solution processed OFETs are fabricated. OFETs with BCDPP show unipolar p-type semiconducting properties with hole mobility of 1.02 x 10(-4) cm(2) V-1 s(-1) and OFETs of BCPzDP exhibit ambipolar charge transport behaviour with optimal saturation hole and electron mobilities of 0.0054 and 0.0013 cm(2) V-1 s(-1), respectively. (C) 2016 Elsevier B.V. All rights reserved.